Pulmonary nocardiosis in Chronic Obstructive Pulmonary Disease: A new clinical challenge. (2016) - Castellana, Giorgio; Grimaldi, Anna; Castellana, Marco; Farina, Claudio; Castellana, Giuseppe
Abstract: Pulmonary nocardiosis (PN) is a rare but severe disease caused by Nocardia spp. Despite the traditional description as opportunistic infection, case reports and case series of pulmonary nocardiosis have recently been reported in immunocompetent patients too, in particular among people with chronic pulmonary diseases such as advanced Chronic Obstructive Pulmonary Disease (COPD). PN is characterized by non-specific symptoms and radiological findings; bacteriological culture can be difficult. For the reasons above, diagnosis of PN is challenging, sometimes resulting in a misdiagnosis of tuberculosis. We report an interesting case of PN in a 75-year-old male with COPD. He complained a 3-months history of fatigue, evening rise in body temperature, night sweats, unexplained weight loss of 5 kg, worsening dyspnea, cough and mucopurulent sputum. The chest X-ray showed multiple nodules with cavitations bilaterally in the apical and subclavian regions. Nocardia cyriacigeorgica with 100% identity was identified in three sputum samples. Since the patient has never undergone a systemic and/or inhaled steroid therapy, and has no respiratory failure and comorbidities entailing immunodepression, it is conceivable that, in this immunocompetent patient, the COPD could represent an isolated risk factor for PN. Risk factors, clinical presentations, radiographic findings, differential diagnosis and review of the literature of PN cases in COPD, pointing out the similarities and differences, are also described.